Analisis Arus Kas Metode Pembayaran Digital Melalui Qris Pada Toko Jempol Badminton Cikoleang - Muhamad Arif Nugraha; Fauziah Septiani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Toko Jempol Badminton Cikoleang is a business specializing in the retail sale of badminton equipment and racket maintenance services in the Cikoleang area of West Java. Founded in 2010 by Mr. Eko, the store aims to meet the local community’s needs for badminton. The store sells a variety of high-quality products such as rackets, shuttlecocks, shoes, sportswear, and badminton accessories from well-known brands. In addition to selling merchandise, Toko Jempol also provides racket maintenance (stringing) services and rents out indoor and outdoor badminton courts. This study was conducted to analyze the impact of implementing QRIS (Quick Response Code Indonesian Standard) on the business’s cash flow. The method used was a qualitative case study with data collection through in-depth interviews and analysis of the store’s financial documents. The research findings show that the use of QRIS has a significant positive impact. This digital payment system has successfully increased the number of transactions and accelerated cash flow into the store. The convenience of cashless transactions makes customers feel more comfortable and encourages them to make more purchases. However, the study also found that the store still needs to pay attention to two important issues: the QRIS transaction fees charged by service providers and the security of digital transactions. Overall, the implementation of QRIS has proven effective in supporting the growth of Toko Jempol Badminton Cikoleang. To achieve greater efficiency and profitability, the store is advised to conduct regular evaluations of QRIS costs and security risks and to continue educating its customers.